Quantification of human upper extremity nerves and fascicular anatomy. Issue 3 (1st April 2017) - Brill, Natalie A.; Tyler, Dustin J.
ABSTRACT: Introduction: In this study we provide detailed quantification of upper extremity nerve and fascicular anatomy. The purpose is to provide values and trends in neural features useful for clinical applications and neural interface device design. Methods: Nerve cross‐sections were taken from 4 ulnar, 4 median, and 3 radial nerves from 5 arms of 3 human cadavers. Quantified nerve features included cross‐sectional area, minor diameter, and major diameter. Fascicular features analyzed included count, perimeter, area, and position. Results: Mean fascicular diameters were 0.57 ± 0.39, 0.6 ± 0.3, 0.5 ± 0.26 mm in the upper arm and 0.38 ± 0.18, 0.47 ± 0.18, 0.4 ± 0.27 mm in the forearm of ulnar, median, and radial nerves, respectively. Mean fascicular diameters were inversely proportional to fascicle count. Conclusion: Detailed quantitative anatomy of upper extremity nerves is a resource for design of neural electrodes, guidance in extraneural procedures, and improved neurosurgical planning. Muscle Nerve 56 : 463–471, 2017